European monetary policy : the ongoing debate on conceptual issues - Clausen, Jens R (2001)
Discusses the decisions the European Central Bank (ECB) made concerning its strategy. Analyses the role of money and its leading indicator properties. Describes the ECB's interest rate policy, the development of money aggregates and inflation in the euro area. Deals with the issue of transparency and credibility. Discusses issues related to the macroeconomic adjustment process within the euro area.